Service behaviour and semen characteristics in cross-bred boars - PANDE, GAURAV; BHATT, V K; THAKUR, M S (The Indian Journal of Animal Reproduction, 2023)
Six cross-bred boars (Large White Yorkshire X Indigenous) were ejaculated at 72 hours interval by the"Gloved hand method" using estrus females as dummies. The mean reaction time and duration of ejaculation was2.72 ± 0.05 and 3.97 ± 0.07 minutes, respectively. The average total semen volume was 161.31 ± 3.29 ml and gelvolume contributed an average of 24.58 ± 0.16 per cent. The average values of pH, sperm concentration, totalsperm per ejaculate, motile sperm percentage and live sperm percentage were 7.61 ± 0.05, 216.25 ± 7.8 million perml, 26.69 ± 1.33 X 109, 79.27 ± 1.26 per cent and 82.07 ± 1.1 per cent, respectively. The gel volume and pHvaried non-significantly. There was significant variation (P
Keywords: Cross-bred boars; Gloved hand method; Semen characteristics; Service behaviour